PRASANGKA: Potensi Pemicu Konflik Internal Umat Islam - Alfandi, M. (IAIN Walisongo Semarang, 2013)
AbstractThis study is about the potential prejudice sparked internal conflict of Muslims,especially between the group Nahdlatul Ulama (NU) and the Council of Tafsir Al-Quran (MTA) in Surakarta. Lately there is a conflict between NU and the MTAcongregation. MTA is questioned by NU in some areas because of the materials andmethods of preaching/dakwah considered to be provocative and less likely toappreciate the difference fiqhiyah and abusive deeds done by NU. From the reasonabove, the conflict between these two Islamic organizations appeared. One of thetriggers that caused the internal conflict among Muslims is the certain group ofMuslims can not understand well the other religious groups, which have differentideological backgrounds; that it affects the way of thinking, behaving and acting thatare different from themselves. As a result, the internal relations marred by religiousconflict, caused by the internal religious prejudice. Similarly, the possibility thatoccurred among the group of NU and MTA.***Penelitian ini adalah tentang potensi memicu prasangka konflik internal umatIslam, terutama antara kelompok Nahdlatul Ulama (NU) dan Majelis Tafsir Al-Quran (MTA) di Surakarta. Akhir-akhir ini ada konflik antara NU dan jemaat MTA.MTA dipertanyakan/diperdebatkan oleh NU di beberapa daerah karena bahandan metode dakwah/dakwah dianggap/cenderung provokatif dan cenderungtidak menghargai perbedaan fiqhiyah dengan perbuatan kasar yang dilakukanoleh NU. Dari alasan di atas, konflik antara kedua organisasi Islam telah terjadi/muncul. Salah satu pemicu yang menyebabkan konflik internal di kalangan umatIslam adalah kelompok tertentu umat Islam tidak bisa memahami dengan baikkelompok agama lain, yang memiliki latar belakang ideologi yang berbeda, sehinggamempengaruhi cara berpikir, bersikap dan bertindak yang berbeda daridiri mereka sendiri. Akibatnya, hubungan internal yang dirusak oleh konflikagama, disebabkan oleh prasangka keagamaan internal. Demikian pula, kemungkinanyang terjadi di antara kelompok NU dan MTA.Keywords: prasangka, konflik internal, NU, MTA